The abnormalities in event-related oscillations in patients with dementia during recognition of emotional facial expressions - Güntekin, Bahar (Elsevier, 2021)
There is clear evidence that normal aging and dementia caninfluence the ability to recognize facial emotions. Different dementiapatients could have different types of disabilities in their emotionalfunctions. The study aimed tofind out how the event-relatedoscillatory response changes with aging and dementia during theemotional paradigm. 25 patients with amnestic-Mild CognitiveImpairment (aMCI), 25 Alzheimer’s Disease patients (AD), 16Parkinson’s Disease patients with mild cognitive impairment(PDMCI), 16 Parkinson’s Disease patients with dementia (PDD) andage, education, gender matched 25 healthy elderly (HE) wereincluded in the study.
Keywords: Emotional Facial Expressions; Dementia During Recognition; Oscillations